Clinical and epidemiological aspects of children hospitalized with severe rotavirus-associated gastroenteritis in Salvador, BA, Brazil - Carneiro,Nadya B. (2005)
Little is known about the epidemiology of severe rotavirus-associated gastroenteritis in Brazil. Given the morbidity associated with this condition and the importance of having detailed knowledge about the impact of rotavirus infection on the epidemiology of acute diarrhea in children, especially those with the most severe diarrheal conditions, we retrospectively reviewed the medical records of all pediatric patients admitted to a tertiary hospital in Salvador, Brazil, due to rotavirus-associated gastroenteritis during one year. It was observed that rotavirus was responsible for 15.6% of the hospitalizations caused by diarrhea and/or vomiting during the period of the study and that 87 of 218 (39.1%) patients seen at the emergency room with rotavirus-associated gastroenteritis needed to be hospitalized, comprising the population of our study. Most patients presented signs of dehydration, and 41% of them had metabolic acidosis. Most patients (79%) were between six months and four years of age and 72% of the cases occurred in June and July. Gastrointestinal symptoms were rarely present at the beginning of the clinical presentation, and they normally did not last for more than one week.